Theatre and modernity: oasis of deceleration - Skjoldager-Nielsen, Daria (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The article analyzes the role of theater in relation to modernity defined as a culture of acceleration, as described by Hartmut Rosa. Referring to the notion of an “oasis of deceleration,” the author argues that theater is a unique space that counters the incessant rush of everyday life. Analyzing various aspects of the theatrical experi-ence, such as its anachronistic form, the live contact with actors and the focus on storytelling, the essay points out that theater offers audiences the opportunity for respite and reflection. However, the author also stresses that theater can serve as both a refuge from the rush and an affirmation of the dominant cult of accelera-tion. The article leads to the conclusion that theater, as a cultural phenomenon, has the potential to both subvert and perpetuate the existing social order.